University College of Osteopathy students' attitudes towards psychosocial risk factors and non-specific low back pain: A qualitative study. (September 2018) - Delion, Tristan Paul Eric; Draper-Rodi, Jerry
Abstract: Objectives: The aim of this study was to explore University College of Osteopathy (UCO)students' attitudes, beliefs and opinions towards psychosocial (PS) factors when treating patients presenting with non-specific low back pain (NSLBP). Methods: A qualitative research design with elements of grounded theory was used. Nine final year UCO students were recruited and interviewed at the UCO teaching centre. Data collection and analysis occurred simultaneously through the constant comparative method of analysis. Results: Three main themes emerged from the data analysis: 1) Definition and interpretation of PS factors towards NSLBP; 2) Assessment and management of PS factors; 3) Competence and difficulties towards PS factors. Conclusions: The level of understanding was homogeneous amongst the participants on the understanding of PS factors and their role in a NSLBP presentation. They assessed for PS factors throughout the case history and tend to rely on their instincts. Two types of strategies towards the PS factors management were identified. However, lack of clinical experience and lack of training on the management of PS factors were identified as the main barriers encountered by students when treating patient with NSLBP. Highlights: Students with a biopsychosocial training show confidence in the psychosocial risk factors assessment. The interpretation of these psychosocial factors is homogeneous amongst students. The main difficulty was including these psychosocial factors into patients' management. Undergraduate curricula should enhance their content on psychosocial management.